Notary's Authority in Making Deeds of Agreement to Protect Trade Secrets - Gitalansa Martantina Widya; Budi Santoso (Fakultas Hukum Universitas Widya Mataram, 2025)
Trade secrets are a crucial element of intellectual property in the modern business world, requiring proper legal protection. One preventive legal tool is a confidentiality agreement (Non-Disclosure Agreement), which can be reinforced through notarial deeds. This research aims to analyze both the role and legal authority of notaries in drafting such agreements and to assess the extent of their contribution to trade secret protection. Using a normative juridical method with statutory and conceptual approaches, this paper examines notarial deeds in light of their legal validity and evidentiary strength. The findings show that notaries, as public officials, possess significant legal authority and play a strategic role not only in formalizing contracts but also in ensuring their enforceability. Their involvement enhances legal certainty and strengthens the legal framework protecting trade secrets in contractual relations.